BERPIKIR DALAM PERSPEKTIF ALQURAN - Malkan, Malkan (Institut Agama Islam Negeri (IAIN) Palu, 2007)
This article deals with Ø§ÙØªÙÙØ± in the Qurâan employing the thematic method of qurâanic exegesis. Observing the verses used the Qurâan, the writer found some words in the Qurâan denoting both negative and positive thinking. To denote the negative thinking, the word ØªØªÙÙØ±ÙÙ is used; to denote the things related to the prohibition of drinking liquor and of gambling; the word ØªØ¹ÙÙÙÙ is used; to denote the order to do good things; the word ÙØ¸Ø± is used; to denote al-Walid al-Mughirahâs negation to the Qurâan; to denote the unbelieversâ accuses of the prophet Muhammad, the word Ø§ØÙØ§Ù is used. In the mean time, to denote the positive thinking, the Qurâan adopts the word ÙØªÙÙØ±ÙÙÂ that is something related to the creature of the universe and of the natural phenomena; the word ÙÙØ¸Ø± is used to denote the origin of human beings; the word Ø§ÙÙÙ Ø§ÙØ§ÙØ¨Ø§Ø¨ is used to denote agreement and negation to truth of the Qurâan.Â Kata Kunci: tafsir, berpikir, Alquran